O conceito de coisa em si na Crítica da Razão Pura e as origens da polêmica que o envolve - Conterato, Luis Sergio Vieira (2017)
This dissertation aims to study the concept of thing in itself in the Critique of Pure Reason and the origins of the controversy that surrounds it. In the light of this scope, this work was elaborated and articulated in three chapters whose purpose was to point out the origins of the controversy that involves the concept of thing itself, the main objectors and their respective objections to the thing itself. Given these questions to the thing itself, we’ve approached Allison's proposal to defend a non-polemical use of the concept of thing itself, from the understanding that the distinction phenomena and thing itself are two ways of considering the same thing. Next, it deals with the construction of the concept of thing itself within the Critique of Pure Reason, addressing the implications of texts of the Preface, Transcendental Aesthetics, Analytic Concepts and Analytic of the Principles for the consolidation of the meaning of the thing considered in itself it. In this sense, the differences between the thing itself, phenomenon, transcendental object and noumenon, and especially in what sense some of these concepts can be used as equivalents in the light of the Critique of Pure Reason, stand out. Finally, the importance of the concept of thing itself in Transcendental Idealism was analyzed, since the criticisms were incisive, but Kant remained with the concept of thing itself in his Theory of Knowledge. Thus, the task of the concept of thing itself in Transcendental Idealism was observed, which led to the conclusion that the thing considered in itself, in spite of the controversies surrounding it, is essential for the success of Kant's critical program, named as Transcendental Idealism whose thesis is the access to the objects of the senses, since these depend on the pure forms of sensibility and the impossibility of the cognoscent subject to scan things considered in themselves, since their existence does not depend on the human faculty of knowledge